The collection of Lidia Falcón: an archive for the history of the feminist movement since the 1960s - Jareño Gila, Claudia (Investigaciones Feministas (Feminist Research), 2019)
One of the greatest challenges in the history of struggles for women’s rights is the collectionand conservation of documents generated by associations, collectives and individuals that were partof the Feminist Movement during the Spanish Transition to democracy. With the aim of highlightingpart of their content, this article presents the Lidia Falcón Fonds as well as the Feminist Party and theFeminist Vindication Club Fonds, available for consultation at the National Archive of Catalonia. Thefonds consist of all the documents produced in many projects led by Falcón –a lawyer, writer, journalistbut also a dramatist and untiring feminist militant– among which we may underline the publication oftwo magazines –Vindicación Feminista y Poder y Libertad– as well as the foundation of the FeministParty of Spain. Therefore, the diversity and volume of documents collected make these two fondsessential for the study and reconstruction of the history of this movement.
Keywords: Archives; feminism; Feminist Vindication; Lidia Falcón